Miselna naravnanost v šolskem okolju - Polh Budja, Katja; Košir, Katja (Revija za elementarno izobraževanje, 2019)
Mindset in School Environment. The mindset comprises the individual’s beliefs about his or her most fundamental characteristics and abilities. Our research was focused on the mindset regarding mental abilities and considered it as a factor of academic achievement, academic self-concept, academic self-regulation and giftedness. The study included 232 primary school pupils from 8th and 9th grade. The results showed that pupils with a higher degree of mindset to growth have better academic achievements and higher academic self-concept compared to pupils who are mainly fixed mindset oriented. The research has shown that the growth mindset and academic self-regulation are positively related. We also found that mindset does not have an incremental predictive value for academic achievement alongside academic self-concept and academic self-regulation. It turned out that gifted pupils mindset is more mentally oriented towards growth compared to their normative peers, and that mindset does not have a moderator effect in predicting academic achievement in relation to identified pupils’ giftedness. DOI: 10.18690/rei.12.1.89-112.2019 COBISS-ID: 24672264 Accepted 8. 1. 2019; Published 26. 3. 2019.